A Case Study of the Stratospheric and Mesospheric Concentric Gravity Waves Excited by Thunderstorm in Northern China - Ying Wen; Qilin Zhang; Haiyang Gao; Jiyao Xu; Qinzeng Li (Atmosphere, 2018)
In this paper, the complete process in which a concentric gravity wave (CGW), excited by a tropospheric thunderstorm, propagated into the stratosphere and mesosphere in Northern China is investigated. A strong thunderstorm developed in the middle of the Inner Mongolia autonomous region on the night of 10th August 2013. The stratospheric temperature perturbation, caused by the CGW, was observed by the Atmospheric Infrared Sounder (AIRS) at 02:11 LT 11th August 2013. An all-sky OH imager at the Shuozhou station (39.8° N, 112.1° E), supported by the Meridian Space Weather Monitoring Project, measured the mesospheric CGW between 22:00 LT to 23:00 LT on the night. It was certified that both the stratospheric and mesospheric CGWs were triggered by the aforementioned thunderstorm, and the excitation source was calculated to be located at (40.59° N, 108.67° E) by employing the dispersion relation. The CGWs were excited in the initial stage of the thunderstorm. The temperature and wind field data obtained by SABER and meteoric radar, respectively, were used to evaluate the background properties of the respective propagation regions. The result shows that an obvious thermal duct structure, with a positive squared vertical wavenumber (m2) existed around the OH layer.